The Effect of Message Framing on Intentions to Quit Smoking with Source Credibility as Moderator (Studies in Student Faculty of Economics and Business, University of Brawijaya) - Failasufi, Faza (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research was motivated by the number of active smokers is increasingly rising. Governments are required in order to deliver a persuasive message to people to stimulate their intention to quit smoking. This study aims to determine the effect of variable message framing on the intention to quit smoking with a variable source credibility as a moderator at the Faculty of Economics and Business, University of Brawijaya.Type of research is explanatory research with quantitative methods. Samples were 70 respondents with a purposive sampling techniques. The method of analysis used multiple regression analysis with SPSS software version 17.0. Test research instruments include validity, reliability, and hypothesis testing. The analysis showed that the Message Framing positive and significant effect on the Intention to Quit Smoking. Source credibility moderates in the form of strengthening relations between the Message Framing on Intentions to Quit Smoking Keywords: message framing, source credibility, intention to quit smoking.